2021
DOI: 10.1111/jcpt.13593
|View full text |Cite
|
Sign up to set email alerts
|

Clinical practice guidelines for management of dual antiplatelet therapy in patients with noncardiac surgery: A critical appraisal using the AGREE II instrument

Abstract: What is known and objective: Despite the availability of clinical practice guidelines (CPGs), there are considerable differences in their recommendations in the perioperative management of stented patients who need elective noncardiac surgery. Our aim was to systematically review the quality of CPGs for perioperative management of dual antiplatelet therapy (DAPT) and summarize the recommendations. Methods: A systematic search for perioperative DAPT guidelines was conducted on PubMed, Embase and websites of gui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…8 In most clinical situations, continuous aspirin provided benefit that outweighed the bleeding risk, so most guidelines recommend that aspirin is continued perioperatively. 3 However, aspirin cessation should be considered when it comes to the procedures associated with a very high risk of hemorrhagic complications, such as a surgical procedure for pulmonary abscess with empyema or pulmonary resection for destructive pneumonophthisis, for which the American Clinical Practice Guidelines suggest stopping aspirin ≤7 days before the surgery, and resuming an antiplatelet agent ≤24 h after the surgery. 4 There was a lack of consensus in a previous study with regard to the use of bridging therapy with heparin or intravenous antiplatelet agents during perioperative antiplatelet cessation, as the bridging therapy demonstrated no clear benefits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 In most clinical situations, continuous aspirin provided benefit that outweighed the bleeding risk, so most guidelines recommend that aspirin is continued perioperatively. 3 However, aspirin cessation should be considered when it comes to the procedures associated with a very high risk of hemorrhagic complications, such as a surgical procedure for pulmonary abscess with empyema or pulmonary resection for destructive pneumonophthisis, for which the American Clinical Practice Guidelines suggest stopping aspirin ≤7 days before the surgery, and resuming an antiplatelet agent ≤24 h after the surgery. 4 There was a lack of consensus in a previous study with regard to the use of bridging therapy with heparin or intravenous antiplatelet agents during perioperative antiplatelet cessation, as the bridging therapy demonstrated no clear benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Available studies report that the effect of perioperative aspirin continuation on thromboembolic and major bleeding events were varied. 2 , 3 With the rapid development of minimally invasive surgical techniques, when patients receiving aspirin are undergoing elective noncardiac surgery, the American Clinical Practice Guidelines suggest aspirin continuation over aspirin interruption. 4 The 2021 Chinese expert collaboration stated that aspirin should not be discontinued during the perioperative period for major tumor surgery and major thoracic surgery for patients with atherosclerotic cardiovascular disease with high or very high risk of ischemic cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic evaluation of 10 guidelines for perioperative management of dual antiplatelet therapy has demonstrated limited rigor and lack of evidence and consensus. 55 The strengths of this systematic review relate to the close working relationship with experts from CHEST/ACCP who developed a priori clinical question and inclusion criteria and. A panel from CHEST/ACCP will use this evidence along with other contextual and implementation factors, such as patients’ values and preferences, feasibility, and acceptability, to develop practical advice for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…We found that stakeholder involvement regarding the experience and expectations of the target population in development of the guidelines was lacking, a limitation also found in the appraisals of other perioperative guidelines. [30][31][32] Consultation with patients helps ensure that values, preferences, and topics of priority have been considered. There has been an increased shift toward a patient-centered approach in the perioperative care setting that aims to take into account the holistic needs and goals of the patient as a means to improve satisfaction, functional status, and well-being.…”
Section: Discussionmentioning
confidence: 99%